2016
DOI: 10.21037/cdt.2016.09.05
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of cardiothoracic surgery practice in Nigeria: a 12 years institutional experience

Abstract: Infections, malignancy and trauma currently account for the bulk of cardiothoracic surgery practice in Nigeria, with surgical activity showing a predominance of minor procedures and comparatively minimal OHS activities. Identified challenges to increasing cardiothoracic surgical activity were limitations in manpower development, infrastructure, laboratory support, local availability of consumables, cost of surgery, funding mechanisms for surgery, multiple models for development of cardiac surgery, decentraliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…From published data, 9 the ACHD age profile seen in Nigeria was similar to the Ghanaian experience ( Table 2). The very low number of previously operated patients is an indication of poor access to cardiac interventions in this country, 10 which incidentally is the country with the highest CHD birth prevalence in Africa.…”
Section: Clinical Profile Of Achd In Africa Regionsmentioning
confidence: 99%
“…From published data, 9 the ACHD age profile seen in Nigeria was similar to the Ghanaian experience ( Table 2). The very low number of previously operated patients is an indication of poor access to cardiac interventions in this country, 10 which incidentally is the country with the highest CHD birth prevalence in Africa.…”
Section: Clinical Profile Of Achd In Africa Regionsmentioning
confidence: 99%
“…This is a common finding in many developing countries, where access to cardiac surgery remains challenging [3,6,8,9]. In a study by Falase et al [7] in Lagos-Nigeria, only 3.4% of patients including adults with structural heart diseases were able to undergo cardiac surgeries. A more recent data from the National Paediatric Cardiac Registry revealed that less than 20% of children who required cardiac interventions actually received the necessary surgery [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is instructive that all the interventions undertaken at our centre were for simple lesions: PDA ligation independently performed by the local team and VSD/ ASD closure undertaken in collaboration with visiting cardiac team. While periodic cardiac mission does provide intermittent relief for a few patients and creates opportunity for some skill transfer [7], it may not adequately cater for the large volume of patients on the waiting list. Comprehensive strategy that will ensure availability of such services locally, and at regular and sustainable basis, is therefore needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations